Keratitis‐ichthyosis‐deafness syndrome: Phenotypic heterogeneity and treatment perspective of patients with p.Asp50Asn GJB2 mutation. Issue 6 (23rd November 2020) - Asgari, Tina; Naji, Mahtab; Mansouri, Parvin; Mahmoudi, Hamidreza; Zabihi, Masoud; Youssefian, Leila; Mahdavi, Mohammadreza; Naraghi, Zahra Safaei; Zeinali, Sirous; Vahidnezhad, Hassan; Uitto, Jouni
Abstract: Keratitis‐ichthyosis‐deafness (KID) syndrome is caused by mutations in the GJB2 gene encoding connexin 26, a component of transmembrane hemichannels which form gap junction channels, critical for cell‐cell communication. Here, we report two patients from two distinct families with KID syndrome with the same GJB2 mutation (p.Asp50Asn); in both cases the mutation was de novo, as the parents depicted the wild‐type allele only. The patients' cutaneous manifestations were strikingly different illustrating the wide spectrum of phenotype of these patients, even with the same GJB2 mutation. One of the patients was treated with acitretin with dramatic improvement in his skin findings, illustrating the role of oral acitretin in treatment of patients with KID syndrome. Collectively, these patients attest to the phenotypic spectrum of KID syndrome, with therapeutic perspective.